“We work whenever we are needed”: exploring social identity and intergroup communication among agricultural producers - Loden, Kory P. (Kansas State University, 2018)
The world relies on agriculture and its producers for food, fuel, and fiber. These agricultural producers make up approximately two percent of the United States population, and they attempt to feed the world even as a minority group (American Farm Bureau, 2017). A growing world population and depleted natural resources challenge the global food system, agricultural producers, and everyone who eats. However, the two percent, who are the most directly involved and knowledgeable, are not talking about the problems or processes of agriculture with others (Higgins, 1991). Feeding the world’s population increasingly will demand personal and collective decision-making that would be aided by a fully engaged and informed public. But only if those in agriculture talk about their livelihoods can we close the communication gap between producers and non-producers and thereby work together to solve the shared problems in and of agriculture. Through qualitative interviews with agricultural producers, this study used Social Identity Theory (SIT) and intergroup communication to explore how producers understood their social identity, as well as how their social identity impacted communication with non-producers. This study is unique in that it uses SIT as the guiding theory, focusing on how agricultural producers identify as compared with the relevant out-group, non-producers. This study finds two major themes in producer self-understandings. First, this study shows that agricultural producers view themselves as high in social status while they presume that others do not afford them the same respect. Second, agricultural producers orient themselves to non-producers in two different ways, including the Determined and the Resigned, with each holding a different sense of their ability to bridge the communication gap. This thesis makes several contributions to communication scholarship and practice. First, the findings suggest that social competition and social creativity—two strategies for gaining and maintaining group status—might have different communication and group-relation outcomes when enacted via direct contact with the out-group. Future research is therefore needed to potentially extend SIT theory in regard to these status strategies. Second, the findings suggest that group members who could speak to the tensions within their social identity engaged with out-group members, also prompting the need for more research to clarify this phenomenon relative to SIT. Third, a striking cleavage between those who seek to engage with the out-group as compared to those who do not merits further study, and this study offers several possible avenues for explaining this difference. Fourth, and more practically, the study suggests that producers ought to be introduced to the concepts of social identity and competition to reduce tensions and to encourage interaction between producers and non-producers.
Keywords: Social Identity Theory; Agricultural producers; Communication; Farmers; RanchersAgriculture